In bloom, online an exploratory study of the Philippine Cut Flower Corporation's http://islandrose.net - Abalos, Ma. Laize-Ar P.; Alminanza, Mark Joseph G.; Macaraig, Christine Elizabeth J.; Samia, Anna Karina M.; Sumagui, Jennifer Christine Rose A. (2008)
E-commerce is the use of the Internet to conduct business. In the Philippines, there is an increasing adoption of e-commerce by small and medium enterprises (SMEs). To explore the SMEs' process of adoption of e-commerce, this study analyzed the integration of the Island Rose Web site (http://islandrose.net) in the business operations of the Philippine Cut Flower Corporation (PCFC). Through an interview with the Island Rose Marketing Director and an analysis of islandrose.net, it was found that certain conditions and processes were necessary for the successful combination of the website and the physical business. An evaluation of islandrose.net from the perspective of its users and other entities is recommended for future research.